2012
DOI: 10.5923/j.cmaterials.20120201.01
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Bamboo Fiber Reinforced Biodegradable Plastics

Abstract: This paper describes tensile properties of bamboo fiber reinforced biodegradable plastics. The unidirectional biodegradable composites were made from bamboo fiber bundles and a starch-based biodegradable resin. The tensile strengths of the composites increased with increasing fiber content up to 70%. The composites possessed extremely high tensile strengths of 265 MPa. The fabrication with emulsion-type biodegradable resin contributed to reduction in voids and fiber contacts in the composites. Moreover, heat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…Based on this report the degradation of the bamboo fiber starts from 140°C butinthisrangehasnotbeenobservedanychangesin young'smodulusalmost constant and independent of the heat treatment condition. In the other research about tensile properties of bamboo fiber reinforced biodegradable plastics by the same author Ochi (2012) [69] shows that the tensile strength of both bamboo fiber and bamboo fiber reinforced plastics decreased at 160°C.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Based on this report the degradation of the bamboo fiber starts from 140°C butinthisrangehasnotbeenobservedanychangesin young'smodulusalmost constant and independent of the heat treatment condition. In the other research about tensile properties of bamboo fiber reinforced biodegradable plastics by the same author Ochi (2012) [69] shows that the tensile strength of both bamboo fiber and bamboo fiber reinforced plastics decreased at 160°C.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Another method used to separate bamboo fi bres is the steam explosion method. In steam explosion, the water contained in bamboo is heated under high temperature and pressure and the pressure is then rapidly released to the atmosphere, so that the water evaporates, shattering the parenchyma inside the bamboo (Ochi, 2012 ). This method is more environmentally friendly compared to the chemical process; however, it is rarely used because it is expensive.…”
Section: Cultivation Of Bamboo Fi Bre Extraction and Surface Modifi mentioning
confidence: 99%
“…Experimentally, tensile test was conducted by Ogihara et al [23] on bamboo fibre composite and it was found that tensile strength increases with increasing weight fibre fraction for wt% of less than 30%. Furthermore, Ochi [24] managed to increase volume fraction of bamboo fibres in a starch-based emulsion-type biodegradable resin up to 70% where after conducting tensile test, the composites gave high tensile strength of 265 MPa and tensile modulus of 12.4 GPa. Sapuan et al [25,26] conducted several experimental procedures to determine mechanical properties of several chemically treated and non-treated natural fibre composites including sugar palm and kenaf.…”
Section: Introductionmentioning
confidence: 99%